Sex-Specific Exposure–Effect Relationship Between Physical Activity and Incident Atrial Fibrillation in the General Population: A Dose–Response Meta-Analysis of 16 Prospective Studies - Wan, Qin; Zhou, Yue; Zhu, Wengen; Liu, Xiao (Frontiers in Cardiovascular Medicine, 2021)
Background: Since evidence regarding the relationship between physical activity (PA) and atrial fibrillation (AF) incidence is inconsistent among studies, we performed a dose-response meta-analysis to comprehensively evaluate the exposure-effect association between PA and incident AF and the potential sex difference in the general population. Methods: The PubMed and Embase databases were searched for eligible studies published up to July 2020 (PROSPERO: CRD42018091692). The nonlinear or linear exposure-effect relationship between PA and AF was examined using the robust error meta-regression method. Results: A total of 16 prospective studies involving 1,449,017 individuals and 39,884 AF cases were included. We observed an inverse nonlinear association between PA level and incident AF (I2=0%, Pnonlinearity<0.001). In the linear model, a 5 metabolic equivalent of task (MET)-h/week increase in PA was associated with a decreased risk of AF (risk ratio [RR]=0.992, 95% confidence interval [CI]: 0.988-0.996, I2=0%). In the sex-stratified analysis, we observed an inverse nonlinear relationship between PA level and AF risk in females (I2=90%, Pnonlinearity<0.0001) but not in males (I2=0%, Pnonlinearity=0.40). In the linear model, a 5 MET-h/week increase in PA was associated with a reduced risk of AF in females (RR=0.982, 95% CI: 0.975-0.989, I2=71%) but not in males (RR: 0.998, 95% CI: 0.994-1.002, I2=0%), with a significant interaction observed between the two groups (Pinteraction < 0.0001). Conclusion: There was an inverse nonlinear relationship between PA level and incident AF in the general population. The beneficial effect of PA in reducing AF risk might be predominantly observed in females.